Swedish Plectida (Nematoda). Part 9. The genus Leptolaimoides Vitiello, 1971 - Holovachov, Oleksandr (Zootaxa, 2015)
Three known and two new species of Leptolaimoides are described from bottom sediments collected in Skagerrak off the west coast of Sweden. The following known species are redescribed: Leptolaimoides haploopis Jensen, 1978, L. tubulosus Vitiello, 1971 and L. hexatubulosus Hoang Lai-Phu et al., 2009. Leptolaimoides filicaudatus sp. n. is characterised by the 431–543 µm long body; cephalic sensilla papilliform; amphid 23–26 µm long, located 9–10 µm from anterior end; first body pore located 35–37 µm from anterior end; lateral field simple along most of body, areolated on tail, arising 36–40 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male without tubular and without alveolar supplements; spicules arcuate and 16 µm long. Leptolaimoides leptomicron sp. n. is characterised by the 776–847 µm long body; cephalic sensilla papilliform; amphid 15–17 µm long, located 9–13 µm from anterior end; first body pore located 40–46 µm from anterior end; lateral field areolated, arising 26–28 µm from anterior end; female without supplements, vagina without pars refringens, vulva midventral; male with three tubular and without alveolar supplements, spicules arcuate and 28–29 µm long. The diagnosis of the genus Leptolaimoides is emended and a tabular compendium and dichotomous identification key to species of the genus Leptolaimoides are provided.